Case report: A case of renal arcuate vein thrombosis successfully treated with direct oral anticoagulants - Torabi Jahromi, Mahsa; Roozbeh, Jamshid; Masjedi, Fatemeh; Mohammadzadeh, Sahand; Tabei, Seyed Sajjad; Shafiee, Maryam; Rasaei, Nakisa (Frontiers in Medicine, 2023)
A rare case of a 35 years old woman presented with renal arcuate vein thrombosis (RAVT) and acute kidney injury (AKI) following upper respiratory tract symptoms and toxic substance ingestion. Histopathological evaluation of the patient’s kidney tissue indicated a rare venous thrombosis in the renal arcuate veins. Anticoagulation with Apixaban, a direct oral anticoagulant (DOAC), was commenced, and the patient’s symptoms resolved during the hospital stay. Hitherto, a limited number of studies have shown the concurrent presentation of RAVT and overt AKI in patients following ingestion of nephrotoxic agents. Further studies are necessary to elucidate the etiology, clinical presentation, and treatment of RAVT. We suggest that Apixaban be studied as a suitable alternative to conventionally used anti-coagulants such as Warfarin in patients who lack access to optimal healthcare facilities.